Preemptive percutaneous coronary intervention for coronary artery disease: identification of the appropriate high-risk lesion. (November 2020) - Pu, Zhongyue; Hakim, Diaa; Croce, Kevin; Stone, Peter H.
Abstract : Purpose of review: Management of patients with coronary artery disease (CAD) has been based on identification of a coronary obstruction causing ischemia and performing a revascularization procedure to reduce that ischemia, with the goal of thereby preventing subsequent major adverse cardiac events (MACEs) in that vascular territory. Recent investigations demonstrate that preemptive percutaneous coronary intervention (PCI) of nonculprit coronary lesions (NCLs) that may not cause ischemia in patients with ST-segment elevation myocardial infarction (STEMI) reduces MACE. In this review, we focus on preemptive PCI, discuss its mechanistic benefits and speculate on its potential value for other coronary syndromes. Recent findings: The COMPLETE trial in STEMI patients treated with primary PCI demonstrated that preemptive PCI of NCL obstructions, which may not cause ischemia, but often exhibit high-risk OCT plaque characteristics, reduced cardiovascular death or nonfatal myocardial infarction. Reduction in MACE from preemptive PCI of NCL was similar for lesions confirmed to cause ischemia (fractional flow reserve <0.80) and for lesions that were only visually assessed to have luminal obstruction at least 70%. The ISCHEMIA trial in patients with stable CAD and moderate/severe ischemia demonstrated that MACE risk increased progressively with more extensive atherosclerosis, but that performing PCI of ischemia-producing lesions did not reduce MACE. Adverse cardiac events likely originated in high-risk plaque areas not treated with PCI. Summary: In STEMI patients, preemptive PCI of high-risk NCL that may not cause ischemia improves long-term MACE. In stable CAD patients, MACE increases as the atherosclerotic burden increases, but PCI of the ischemia-producing lesion itself does not improve outcomes compared with optimal medical therapy. Adverse events likely originate in high-risk plaque areas that are distinct from ischemia-producing obstructions. Identification of highest-risk atherosclerotic lesions responsible for future MACE may provide an opportunity for preemptive PCI in patients with a variety of coronary syndromes.